PENERAPAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR DALAM PEMBELAJARAN SENI BUDAYA - Nursakinah, Tsani; Syarif Hidayat, Ujang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of using audiovisual media in improving learning outcomes of elementary school students in Cultural Arts subjects. This research uses a literature review method sourced from various relevant national scientific journals between 2019 and 2025. Data was collected through searching articles using certain keywords such as "learning outcomes", "audiovisual media", and "elementary cultural arts". The results of the analysis show that the use of audiovisual media, such as learning videos, interactive animations, and other audio-visual recordings, is able to improve student learning outcomes in cognitive, affective, and psychomotor aspects. The increase in learning outcomes can be seen from the pretest and posttest scores which have increased significantly after the application of this media. However, some of the obstacles faced are limited facilities, lack of teacher understanding, and not maximizing the integration of technology in learning. This study provides evidence that the effective use of audiovisual media can support the improvement of learning quality and students' attraction to Cultural Arts materials in elementary schools.